1994
DOI: 10.1002/j.1460-2075.1994.tb06848.x
|View full text |Cite
|
Sign up to set email alerts
|

Three residues in the common beta chain of the human GM-CSF, IL-3 and IL-5 receptors are essential for GM-CSF and IL-5 but not IL-3 high affinity binding and interact with Glu21 of GM-CSF.

Abstract: The beta subunit (beta c) of the receptors for human granulocyte macrophage colony stimulating factor (GM‐CSF), interleukin‐3 (IL‐3) and interleukin‐5 (IL‐5) is essential for high affinity ligand‐binding and signal transduction. An important feature of this subunit is its common nature, being able to interact with GM‐CSF, IL‐3 and IL‐5. Analogous common subunits have also been identified in other receptor systems including gp130 and the IL‐2 receptor gamma subunit. It is not clear how common receptor subunits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
89
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 35 publications
14
89
0
Order By: Relevance
“…Accordingly, the low affinity site K d was fixed at 100 nM during analysis in LIGAND in order to obtain a more accurate estimate of the high affinity site (K d , 107 pM). The dissociation constants we obtained are consistent with those reported in previous studies (28,30) on the hIL-3 receptor. The h␤c subunit used in these studies was derived from HL-60 eosinophils and contained a six-amino acid insertion in the C-D loop of domain 3 (34).…”
Section: Il-3-binding Epitopes Of M␤ Il-3 and H␤csupporting
confidence: 91%
See 2 more Smart Citations
“…Accordingly, the low affinity site K d was fixed at 100 nM during analysis in LIGAND in order to obtain a more accurate estimate of the high affinity site (K d , 107 pM). The dissociation constants we obtained are consistent with those reported in previous studies (28,30) on the hIL-3 receptor. The h␤c subunit used in these studies was derived from HL-60 eosinophils and contained a six-amino acid insertion in the C-D loop of domain 3 (34).…”
Section: Il-3-binding Epitopes Of M␤ Il-3 and H␤csupporting
confidence: 91%
“…COS7 cells expressing the wild-type h␤c and hIL-3␣ receptors exhibited two binding sites. In agreement with earlier studies, it was found that accurate estimation of the low affinity site is not possible because of its very low K d values (ϳ100 nM) resulting in a high associated error (28). Accordingly, the low affinity site K d was fixed at 100 nM during analysis in LIGAND in order to obtain a more accurate estimate of the high affinity site (K d , 107 pM).…”
Section: Il-3-binding Epitopes Of M␤ Il-3 and H␤csupporting
confidence: 83%
See 1 more Smart Citation
“…Several receptors in the cytokine receptor family have residues important for ligand binding located in the loop between the BЈ and CЈ ␤-strands (5,12,14). We have reported previously that Ser 152 in the BЈ-CЈ loop of the EPOR may have a role in EPO binding, based on the 16-fold increase in IC 50 value of the S152A-EBP (15).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of many of these ligand binding determinants was subsequently confirmed in structural studies. For example, Woodcock et al (12) used alanine substitution mutagenesis on the common ␤-chain (␤ c ) of the human GM-CSF, IL-3, and IL-5 receptors to identify amino acid residues critical for the formation of the high affinity receptors for GM-CSF and IL-5. Using mutation complementation, they also identified a residue in GM-CSF that is likely to interact with the critical residues on the ␤ c .…”
mentioning
confidence: 99%